Environmental efficiency of ports under the dual carbon goals: Taking China’s Bohai-rim ports as an example - Li, Jinpei; Ren, Jianing; Ma, Xun; Xiao, Guangnian (Frontiers in Marine Science, 2023)
In 2020, China proposed the country’s dual carbon goals of peaking carbon emissions by 2030 and achieving carbon neutrality by 2060. Under the dual carbon goals, the low-carbon transformation has become an important development direction for Chinese ports. Taking eight ports in China’s Bohai-rim port group as an example, this study adopts the Slacks-Based Measure (SBM) model to evaluate the port efficiency considering the environmental factor of carbon dioxide (CO2) emissions. The results show that the average scale environmental efficiency of the eight ports during 2005-2020 is the highest, followed by local pure technical environmental efficiency and global technical environmental efficiency. The efficiency values of each port under different environmental efficiency categories vary greatly. Overall, each port is in a state of environmental inefficiency. From port technology, input-output optimization, supervision, and management of relevant departments, recommendations for improving the environmental efficiency of ports under the dual carbon goals are put forward.